Phenomenological exploration of low conceptual understanding in mathematical story problem-solving among Indonesian Junior High School Students - Siti Rauhun; Indrawati Indrawati; Bahri Samsul; Sudirman Sudirman; Ronaldo Rafael Olivero-Acuña (Nashir Al-Kutub Indonesia, 2025)
Mathematical story problems present persistent challenges for students worldwide, yet little research explores how students with low conceptual understanding subjectively experience these difficulties. This phenomenological study investigated the lived experiences of 15 Indonesian Grade VIII students (ages 13-15) with low conceptual understanding in mathematical story problem-solving. Using open-ended questionnaires and reflexive thematic analysis, we explored students’ perceptions and challenges in a private junior high school in West Lombok Regency, Indonesia. Three interconnected themes emerged: (1) Internal Psychological Barriers—mathematics anxiety, fixed mindset beliefs, and internalized failure attributions; (2) Cognitive and Linguistic Challenges—difficulties in text comprehension, mathematical representation, strategic knowledge, and multi-step reasoning; and (3) Glimpses of Interest—unexpected positive affective responses to story contexts despite struggles. Findings reveal that low conceptual understanding is not a unitary cognitive deficit but a complex, multi-dimensional phenomenon involving cognitive, affective, linguistic, and motivational dimensions. Students experience multiple, compounding obstacles while carrying emotional burdens that further impede learning. By centering student voice, this study illuminates subjective realities that quantitative achievement data alone cannot capture. Implications suggest effective interventions must comprehensively address conceptual skills, affective barriers, linguistic demands, and motivation simultaneously. For Indonesian contexts, findings call for reconsidering traditional approaches prioritizing procedural fluency over conceptual understanding and student wellbeing. This research advances phenomenological methodology in mathematics education and provides actionable insights for developing responsive, equity-oriented instruction.